Cover Feature: Rational Functionalization Towards Redox‐Active TEMPO Stable Free‐Radical‐Hydrochar Composites (ChemSusChem 9/2021). Issue 9 (15th April 2021) - Patrinoiu, Greta; Calderon‐Moreno, Jose M.; Somacescu, Simona; Musuc, Adina M.; Spataru, Tanta; Ionita, Petre; Carp, Oana
Abstract : The Cover Feature shows the hydrothermal transformation of a binary system composed of a biomass component and a stable nitroxide free radical into a blackberry‐like hydrochar. This simple, green, sustainable one‐pot process integrates the radical species onto/into the carbonaceous matrix that demonstrates enhanced properties in terms of both electrocatalytic activity and capacitive features. More information can be found in the Full Paper by G. Patrinoiu et al .